Strategi Pembelajaran Langsung (Konvensional) - Muslimin, Rika Rahayu; Usman, Syahruddin; Rama, Bahaking (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The role of teachers in the world of education is very important and is not limited to teaching material. Teachers must have skills in classroom management and effective learning strategies to create a conducive classroom atmosphere, which contributes to the success of learners in understanding the lessons. One of the methods that is often used is direct learning, where the teacher acts as a facilitator who directs and supports students' learning activities in a structured and logical manner. The purpose of this study is to find out the definition of direct learning strategies, the characteristics of direct learning strategies, the theoretical foundations of direct learning strategies, the types of direct learning strategies, the steps to implement direct learning strategies and the advantages and disadvantages of direct learning strategies. The method used in this study is qualitative descriptive with a literature study approach by utilizing databases derived from previous writing sources, such as library books, to collect data. The results of the study show that the direct learning strategy is a teaching approach in which the teacher plays a central role in delivering material directly to students. The hands-on learning strategy uses modeling and demonstration to learn through observation, guided by teachers who focus on delivering the material comprehensively. The active participation of students is very important. This approach is based on theories such as constructivism, behaviorism, cognitivism, social learning theory, and problem-based learning. This model includes orientation, material presentation, structured exercises, guided exercises, and independent exercises. Although effective in controlling the material and teaching concepts to low-achieving learners, this strategy also has limitations in active social interaction and teaching complex material.